Anticancer Effect of Ascidian Aplidium Species Extract against Ovarian and Breast Cancer Cell Lines - Gaurav Makrand Thoke; Palati Sinduja; Kumaravel Kaliaperumal; Swati Gandham; Subhashri Rajasekar; Pavithra Murugesan (Journal of Pharmacy and Bioallied Sciences)
Introduction: Cancer continues to pose a significant challenge in the field of medicine, demanding innovative approaches and novel therapeutic avenues for effective treatment. Within this landscape, the exploration of natural compounds derived from marine organisms has garnered attention for their potential anti-cancer properties. Aim: Our present study aims to evaluate the pharmacological effect of Aplidium species in terms of anti-cancer properties which are assessed through biochemical methods. Materials and Methods: The sample was collected from the Thiruchender coastal areas. It was then washed and extracted with methanol which then was used for biological screening against two cancer strains, namely, MCF-7 (Breast cancer cell line) and A2780 (Ovarian Cancer cell line). Conclusion: Alpidium sp extract has significant anticancer effect against two different cancer cell lines when compared to standard drugs.